1995
DOI: 10.1042/bj3100795
|View full text |Cite
|
Sign up to set email alerts
|

Early signalling events implicated in leukotriene B4-induced activation of the NADPH oxidase in eosinophils: role of Ca2+, protein kinase C and phospholipases C and D

Abstract: The early signalling events that may ultimately contribute to the assembly and subsequent activation of the NADPH oxidase in guinea-pig peritoneal eosinophils were investigated in response to leukotriene B4 (LTB4). LTB4 promoted a rapid, transient and receptor-mediated increase in the rate of H2O2 generation that was potentiated by R 59 022, a diradylglycerol (DRG) kinase inhibitor, implicating protein kinase C (PKC) in the genesis of this response. This conclusion was supported by the finding that the PKC inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Given the inhibitory effect of DPI on LTB 4 -induced cell migration and ERK activation, we suggest that NADPH oxidase is the primary source of the ROS generated in response to LTB 4 . Consistent with that idea, several studies have shown that LTB 4 promotes robust, receptor-mediated activation of NADPH oxidase (35)(36)(37), which in eosinophils mediates activation of PKC, phospholipases C and D, and cPLA 2 (35,38).…”
Section: Discussionmentioning
confidence: 61%
“…Given the inhibitory effect of DPI on LTB 4 -induced cell migration and ERK activation, we suggest that NADPH oxidase is the primary source of the ROS generated in response to LTB 4 . Consistent with that idea, several studies have shown that LTB 4 promotes robust, receptor-mediated activation of NADPH oxidase (35)(36)(37), which in eosinophils mediates activation of PKC, phospholipases C and D, and cPLA 2 (35,38).…”
Section: Discussionmentioning
confidence: 61%
“…These observations suggest that LTB4-induced ROS generation occurring via NOX is crucial to cell chemotaxis (34,35). In addition, Giembycz has reported that LTB4 promotes the robust, receptor-mediated activation of NADPH oxidase in guinea pig eosinophils (21,36). LTB4 has also been previously shown to promote the phosphorylation and translocation of p47phox, thereby stimulating NADPH oxidase (22).…”
Section: -Lox Metabolites and Reactive Oxygen Speciesmentioning
confidence: 85%
“…Previous results suggest that LTB 4 can evoke a rapid, transient and concentration-dependent generation of H 2 O 2 from eosinophils in suspension (Perkins et al, 1995;Lindsay et al, 1998a,b;Lynch et al, 2000). Using guinea-pig eosinophils incubated upon 96-well plates coated with BSA, near identical rapid superoxide release, as measured by lucigenin-enhanced chemiluminescence was observed.…”
Section: Discussionmentioning
confidence: 96%
“…GF 109203X was particularly e ective thus implicating a role for both conventional and novel isoforms of PKC. Previous studies have demonstrated similar e ects of PKC on other functions such as Ca 2+ transients, homotypic aggregation, oxidative burst and eicosanoid production in guinea-pig and human-eosinophils (Perkins et al, 1995;Teixeira et al, 1997;Dent et al, 1998).…”
Section: British Journal Of Pharmacology Vol 134 (4)mentioning
confidence: 88%
See 1 more Smart Citation